The preoperative hemoglobin, albumin, lymphocyte, and platelet score (HALP) as a prognostic indicator in patients with non-small cell lung cancer - Liu, Qiteng; Xie, Hailun; Cheng, Wenjuan; Liu, Tong; Liu, Chenan; Zhang, Heyang; Lin, Shiqi; Liu, Xiaoyue; Tian, Haiying; Li, Xiangrui; Zheng, Xin; Chen, Yue; et al. (Frontiers in Nutrition, 2024)
Background: The hemoglobin, albumin, lymphocyte, and platelet score (HALP) is an inflammatory nutrition-related biomarker based on hemoglobin and albumin levels, and lymphocyte, and platelet load index, reportedly related to the prognosis of multiple types of tumors. This study investigates the prognostic value of HALP in patients with non-small cell lung cancer (NSCLC).Methods: A total of 2428 patients with NSCLC were enrolled in the INSCOC study. Time-patient survival trends were validated using Kaplan-Meier curves and log-rank tests. The Restricted Cubic Spline function was used to analyze the relationship between the HALP index and overall survival (OS). The Cox regression model was used for univariate and multivariate analyses.Results: 2053 patients with detailed biological information and follow-up data were included in the study, comprising 1346 men (65.6 %) and 707women (34.4 %). The optimal cut-off for HALP was 29.71, with a sensitivity of 53.1% and specificity of 62.9%, categorizing patients into low (<29.71) (n=963) and high (≥29.71) (n=1090) HALP groups. Patients with a high HALP exhibited significantly higher 5-year OS than those with a low HALP (38% vs.23%, p < 0.001). Multivariable Cox proportional hazards regression analysis revealed low HALP was an independent risk factor for survival of NSCLC.The HALP index can be used as an independent prognostic factor for patients with NSCLC, offering clinicians a reference to identify high-risk patient with poor long-term prognoses and improve individualized treatment.